Analysis of the curve of Spee and the curve of Wilson in adult Indian population: A three-dimensional measurement study - Sowmya Velekkatt Surendran; Sharmila Hussain; S Bhoominthan; Sanjna Nayar; Ragavendra Jayesh (Wolters Kluwer Medknow Publications, 2016)
Statement of Problem: When reconstructing the occlusal curvatures dentists often use a 4-inch radii arc as a rough standard based on Monson spherical theory. The use of an identical radius for the curve of Spee for all patients may not be appropriate because each patient is individually different. The validity of application of this theory in the Indian population and the present study has been undertaken. Aims and Objectives: This study is an attempt to evaluate the curve of Spee and curve of Wilson in young Indian population using three dimensional analysis. This study compared the radius and the depth of right and left, maxillary and mandibular curves of Spee and the radius of maxillary and mandibular curves of Wilson in males and females. Materials and Methods: The cusp tips of canines, buccal cusp tips of premolars and molars and palatal/lingual cusp tips of second molars of 60 maxillary and 60 mandibular casts were obtained. Three-dimensional (x, y, z) coordinates of the cusp tips of the molars, premolars, and canines of the right and left sides of the maxilla and mandible were obtained with three dimensional coordinate measuring machine. The radius and the depth of right and left, maxillary and mandibular curves of Spee and the radius of maxillary and mandibular curves of Wilson were measured by means of computer software Metrologic-XG. Pearson's correlation test and Independent t-test were used to test the statistical significance (α=.05). Conclusion: The values of curve of Spee and curve of Wilson in Indian population obtained from this study were higher than the 4 inch (100 mm) radius proposed by Monson. These findings suggest ethnic differences in the radius of curve of Spee and curve of Wilson.